Metabolomic analysis of Agkistrodon haly venom poisoning mouse treatment by Jidesheng snake pill based on GC-MS - Luo, Jie; Guo, Minkang; Xie, Ke; Han, Ting-Li; Ai, Shanmu (Frontiers in Pharmacology, 2024)
Snakebites are acute systemic toxic diseases caused by snake venom entering the body through wounds. Failure to use antivenom immediately and difficulty in obtaining antivenoms are frequently responsible for worsening disease. Traditional Chinese medicine is commonly used to supplement and replace antivenom in treating snakebites. The Jidesheng snake pill (JDS) is a widely used traditional Chinese medicine that has achieved good clinical therapeutic effects; however, its mechanism remains unclear. Therefore, metabolomics techniques were employed to explore the pathophysiological mechanisms of JDS treatment of Agkistrodon halys (Ah) snake venom-poisoned mice. The Ah group mouse model was established by intramuscular injection of Ah venom into the hind legs of the mice. The Ah venom + JDS group model was established using JDS after the affected area was treated with Ah venom. Hematoxylin and eosin (HE) staining was used to evaluate the severity of gastrocnemius injury. Quantitative polymerase chain reaction (qPCR) was utilized to detect the mRNA expression of vascular cell adhesion molecule-1 (VCAM-1), muscle-specific creatine kinase (CKM), thrombin antithrombin complex (TAT), and tumor necrosis factor-alpha (TNF-α). Gas chromatography-mass spectrometry (GC-MS) was performed with multivariate statistical analysis to provide new insights into the global metabolic profile of Ah venom-poisoned mice. HE staining revealed increased red cell necrosis, local hemorrhage, and neutrophil infiltration in the Ah venom group than in the control group. Several compounds were identified, including lipids, amino acids, peptides, and organooxygen. Eighty differential metabolites were screened between the control group and the Ah venom group, and 24 were screened between the Ah venom and JDS groups. The mechanism of Ah venom poisoning in mice may involve aminoacyl-tRNA biosynthesis, various amino acid metabolism disorders, tricarboxylic acid circulation disorders, and abnormal fatty acid metabolism. JDS may reduce symptoms by affecting long-chain fatty acid and amino acid metabolism and promoting nicotinamide-nicotinamide metabolism. Our results suggest that metabolomics has huge prospects for elucidating the pathophysiology of Ah venom.